Microstructure and its effect on mechanical and thermal properties of Al-based Gd2O3 MMCs used as shielding materials in spent fuel storage. Issue 9 (15th June 2020) - Cong, Shuo; Li, Yipeng; Ran, Guang; Zhou, Wei; Feng, Qijie
Abstract: In this study, novel Al-based Gd2 O3 metal matrix composites were designed and synthesized using powder metallurgy to overcome the shortcomings of common neutron absorbers used as shielding materials in spent fuel storage. With an increase in the ball-milling time, the size of powder particles was gradually refined to nanometer scale. Meanwhile, monoclinic Gd2 O3 was induced by collision pressure and, according to dynamic analysis, the solid solution was inconspicuous. Al3 Gd and Gd3 Al5 O12 were formed during ball-milling, which was further accelerated during sintering because thermodynamics analysis indicated that the reaction was endothermic. The microstructures of powder mixtures and sintered bulks were seen. Particles of various shapes were found to be dispersed in the bulk matrix; their shapes and sizes varied with milling time, sintering time and temperature, and concentration of Gd2 O3 . With the increase in sintering temperature and time, the number of porosities and nanoparticles were found to decrease, whereas the sizes of the particles increased. The microhardness of the samples prepared under various conditions was measured, and its relationship with the microstructure was analyzed. It was found that microhardness was positively correlated with the areas of the particles, whereas it was negatively correlated with their sizes. Further, the thermal parameters of the sintered bulks were also measured and the effect of their microstructure and components was analyzed.